Clinical features of rheumatic heart disease in children and adults in Western Ukraine (Bangladesh Journal of Medical Science, 2018)
Background: Rheumatic heart disease (RHD) is still a big problem affecting children and adults in many countries all over the world.Objectives: The aim of our study was to determine the clinical course of RHD in children and adults of Western Ukraine, to ascertain the reasons for development and progression of the disease, and outline prospects for its prevention.Material and methods: The study included 32 children aged 11 to17 years and 35 adults aged 20 to 42 years with RHD. All patients underwent a standardized examination protocol, which consisted of detailed medical history, laboratory tests, ECG, Doppler echocardiography.Results: The mean age in the children group was 15.8±1.5 years and in adults group - 35.4±7.3 years. Rural areas residents were the majority in both children and adults groups, 71.9% and 77.1% respectively. Recurrent acute rheumatic fever (ARF) was observed in 35.0% of children and in 54.3% adults with history of ARF. Long-term secondary prevention of streptococcal infections was satisfactory in 40.0% of child cases and in 31.6% of adult cases. The lack of compliance and poor health awareness among patients and their parents were most common reasons for inadequate prophylaxis. Subclinical RHD was diagnosed in 37.5% of child cases and in 45.7% of adult cases. Isolated mitral regurgitation (MR) was common in child cases (43.8%) while mitral stenosis (MS) (isolated or combined) was the most common in adult cases (88.6%). Clinical signs of heart failure were absent in half of child cases, but were present in all adult cases at functional class II and III (42.3% and 57.7% respectively). Atrial fibrillation occurred in 34.3% of adult cases.Conclusion: MR is the predominant cardiac valvular lesion in children with RHD. Inadequate secondary prevention was identified as one of the main causes of development and progression of the disease, leading in adults to MS, combined valvular lesions, arrhythmic and infectious complications. Education of patients and their parents is very important for improving compliance with long-term prophylaxis. Special attention should be given to patients from rural areas and those with difficulties in adhering to antibiotic prevention regimes.Bangladesh Journal of Medical Science Vol.18(1) 2019 p.87-93